The Effect of Extra Virgin Olive Oil on Reducing Malondialdehyde Levels and Liver Histopathology in Male Rattus Norvegicus with Hypercholesterolemia - Lister, Gilbert; Adinda, Adinda; Djohan, Djohan; Yuliansyah, Jeri (Poltekkes Kemenkes Palu, 2024)
All living things age physiologically. Free radicals attack cells as they age, causing damage, disruption, and death. Free radicals oxidize and damage cell membrane lipids. The body needs optimum antioxidants during oxidative stress. This study hypothesizes EVOO can lower MDA and total cholesterol and repair liver histopathology in hypercholesterolemic Wistar male rats—this research with a pre-post-test control group experiment. The study found that the control group's MDA level was 0.14 ± 0.03 nmol/ml before treatment (pretest), while the group given standard meal for mice and distilled water/day/head for 14 days had a drop to 0.13 ± 0.10 nmol/ml. In treatment group 1, the average MDA level was 0.73 ± 0.03 nmol/ml before treatment, and after 14 days of high-fat, high-cholesterol meal without EVOO, the average MDA level was 0.73 ± 0.03 nmol/ml and dropped to 0.48 ± 0.10 nmol/ml. Treatment group 2 had an average MDA level of 0.22 ± 0.02 nmol/ml before treatment, but after receiving a high-fat, high-cholesterol diet and a 1cc dose of EVOO for 14 days, it decreased to 0.17 ± 0.02 nmol/ml. Before therapy, the mean MDA level in group 3 was 0.17 ± 0.02 nmol/mL. Giving mice a lot of fat and cholesterol and a two cc dose of EVOO for 14 days lowered their MDA levels to 0.08 ± 0.01 nmol/ml, ranging from 0.10 to 0.05. The research concluded that average MDA decreased significantly in treatment group 3 after mice were fed high-fat, high-cholesterol feed and given two ccs of EVOO.